2005
DOI: 10.1152/jn.00954.2004
|View full text |Cite
|
Sign up to set email alerts
|

DrosophilaCAKI/CMG Protein, a Homolog of Human CASK, Is Essential for Regulation of Neurotransmitter Vesicle Release

Abstract: Vertebrate CASK is a member of the membrane-associated guanylate kinase (MAGUK) family of proteins. CASK is present in the nervous system where it binds to neurexin, a transmembrane protein localized in the presynaptic membrane. The Drosophila homologue of CASK is CAKI or CAMGUK. CAKI is expressed in the nervous system of larvae and adult flies. In adult flies, the expression of caki is particularly evident in the visual brain regions. To elucidate the functional role of CASK, we employed a caki null mutant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
1
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 57 publications
4
42
1
2
Order By: Relevance
“…307/313 animals lacking most of the CASK locus, as well as having lesions in other genes, have previously been shown to display motor deficits (Martin and Ollo 1996;Zordan et al 2005;Sun et al 2009) and difficulty habituating (Lu et al 2003;Zordan et al 2005). The causal role of mutation of CASK in these behavioral defects, as well as the role of the two gene products, had never been rigorously tested using a single-gene mutant or genetic rescue, nor had the cellular locus of CASK action been determined.…”
Section: P-element Excision Eliminates the Cask-b Isoformmentioning
confidence: 99%
See 1 more Smart Citation
“…307/313 animals lacking most of the CASK locus, as well as having lesions in other genes, have previously been shown to display motor deficits (Martin and Ollo 1996;Zordan et al 2005;Sun et al 2009) and difficulty habituating (Lu et al 2003;Zordan et al 2005). The causal role of mutation of CASK in these behavioral defects, as well as the role of the two gene products, had never been rigorously tested using a single-gene mutant or genetic rescue, nor had the cellular locus of CASK action been determined.…”
Section: P-element Excision Eliminates the Cask-b Isoformmentioning
confidence: 99%
“…Loss of CASK also produces a gross locomotor deficit (Martin and Ollo 1996;Sun et al 2009), but the cellular circuitry affected by loss of CASK has not yet been identified. Flies missing the CASK gene also show abnormally long responses to stimulation of the giant fiber pathway, the multisynaptic behavioral circuit that underlies the adult escape response (Zordan et al 2005). While the molecular cause of the locomotor deficit following the disruption of CASK expression is still unclear, interaction via the PDZ domain with Drosophila neurexin (or dnrx) at the presynaptic terminals of the neuromuscular junction has been recently suggested as a candidate mechanism for the larval locomotor defect (Sun et al 2009).…”
mentioning
confidence: 99%
“…Walking optomotor test: The optomotor response was tested as in Sandrelli et al (2001), with modifications as in Zordan et al (2005). For each genotype 20 individuals (10 for each sex) were tested.…”
Section: Behavioral and Physiological Analysesmentioning
confidence: 99%
“…Electroretinogram: All experiments were done as described in Zordan et al (2005). Recorded signals were amplified with an intracellular amplifier (705; WPI Instruments), fed to a signal conditioner (CyberAmp; Axon Instruments), lowpass filtered (3 kHz), and then fed to a personal computer through an A/D converter (Digidata 1200; Axon Instruments).…”
Section: Physiological Investigationsmentioning
confidence: 99%
“…Moreover, analysis of CASK mutations in Drosophila melanogaster and C. elegans suggested several other functions. In Drosophila, CASK mutations produce a discrete neurological phenotype that includes aberrant regulation of activities mediated by calcium/calmodulin-dependent kinase II (15,16), and CASK may function by modulating Ca 2ϩ -calmodulin dependent protein kinase (17). In contrast, in C. elegans the CASK homolog Lin-2 is selectively required for vulval differentiation and proper localization of the EGF receptor LET-23 (5).…”
mentioning
confidence: 99%